Interpreting the Passover in the Exodus tradition amongst the TIV as a narrative concerning origin and migration - Weor, Jonathan Tyosar (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.